آية الحقوق العشرة - دراسة تحليلية وموضوعية - هنيات, بلقيس; زينب, مناعي بنت علي; كروش, مروة (جامعة الوادي university of eloued, 2014)
تعد قضية الحقوق من أهم القضايا التي سبق القرآن الكريم إلى تأصيلها وحفظها ومراعاتها؛ كيف والمولى يقول: لعل من أهم الآيات التي تناولت هذا الموضوع آية الحقوق العشرة. لذلك كان موضوع بحثنا هذا دراسة آية الحقوق العشرة دراسة تحليلية وموضوعية للتعرف على مضمونها وأهم المسائل التي عالجتها. بحيث تطرقنا في القسم الأول تفسير الآية تفسيرا تحليليا من سبب نزول ووجه تسمية..؛ أما القسم الثاني تناولنا الدراسة الموضوعية للآية والحقوق العشرة التي اشتملت عليها؛ من تعريف بالحق وصاحبه و الجوانب التي اهتم بها القرآن الكريم في تقرير الحق لصاحبه، وذلك بجمعنا الآيات التي لها علاقة بالقضية المعالجة وتصنيفها موضوعيا ومراجعة أقوال المفسرين في هذه الآيات. لكن تحديدكم لعدد الصفحات جعلنا لم نعطي الموضوع حقه في الدراسة، فاقتصرنا مثلا في بعض الحقوق ذكر أهم الآيات التي تقر الحق لصاحبها وتصنيفها دون التعريج على أقوال المفسرين فيها. إذن ما زال الموضوع بحاجة إلى إثرائه بالأدلة وأقوال المفسرين. ملخص البحث Research Summary The issue of the rights is one of the most important issues that Quran has the precession in its establishing, saving and observing ; how and god says : ( We have not neglected in the Register a thing. Then unto their Lord they will be gathered). Perhaps one of the most important verses that handle this subject is the verse of ten rights : god says. (Worship Allah and associate nothing with Him, and to parents do good, and to relatives, orphans, the needy, the near neighbor, the neighbor farther away, the companion at your side, the traveler, and those whom your right hands possess. Indeed, Allah does not like those who are self-deluding and boastful).. Therefore the subject of our research was the studying of the ten rigths verse analytical and objective study for identifying its content and the most important issues dealt with . In the first section we interpreted the verse analytical interpretation consisting of the reason of the descent, the fact of naming ……… . On the other hand, the second section dealt with the objective study of the verse and the ten rights included in. This study discussed the definition of the right and its owner moreover, the aspects concerned by Quran in determining the right to its owner. For that reason, our work was to bring together the verses which have a relation with the handled issue afterwards, classify them objectively and review the commentators statements concerning these verses. But, your limitation to the number of pages was a prevention for us in giving the subject a deserved study. This made our work restricted. For example, in some rights we just mentioned the most important verses which determine the right to its owner and classify them without a stopover in the commentators statements concerning them. Consequently, the subject still needs enrichment with evidences and statements of the commentators.